ICTs thúc đẩy tiếp cận tín dụng ngân hàng của các hộ kinh doanh du lịch cộng đồng ở Tây Bắc: Hàm ý chính sách kết nối cung - cầu dịch vụ ngân hàng số ở nông thôn Việt Nam. - Đỗ Xuân, Luận; Dương Hoài, An; Trần Mạnh, Hải; Phạm Thái, Thủy (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This study analyzes the effects of the adoption of information and communication technologies (ICTs) on the access to bank credit of the family-owned community-based tourism businesses in Northwestern Vietnam. Data were collected through a survey of 370 households using pre-designed survey questionnaires. The ICTs adoption index is estimated by Principal Component Analysis (PCA) based on 11 component variables, which comprehensively reflect different aspects of ICTs such as the adoption of smartphones, computers, Internet, Zalo, and Facebook. The ICTs index is included as an explanatory variable in the two-step Heckman selection model. Addressing the problem of endogeneity, selection bias as well as including control variables, the estimation results show that ICTs have a positive impact on family-owned community-based tourism businesses’ access to bank credit. In the context of the digital transformation trend, the development of digital banking services based on ICTs adoption can relax access constraints to bank credit by family-owned community-based tourism businesses, thereby sustain poverty reduction.